Anti-bacterial activity of pithecellobium bubalinum in several preparations of seed intake / Siti Nazeha Ahmad Poad - Ahmad Poad, Siti Nazeha (Faculty of Applied Sciences, 2017)
P. bubalinum has a bitter taste and stinky smell as this species from the same family of Parkia speciosa and P. jiringa. This three seed can be eaten raw as ulam or be prepared in several method before the intake. Research has been conducted to determine the anti-bacterial properties of P. bubalinum seeds extract against Grampositive and Gram-negative bacteria by using disc diffusion method as well as to compare the effect of anti-bacterial properties of P. bubalinum seeds extract between three ways preparation of intake which is raw, heated and curing in soil. The concentration of crude extract is 100% while the positive control use is tetracycline and nitrofurantoin and the negative control is distilled water. The result show formation of inhibition zone towards Gram-positive bacteria which is S. aureus is larger with 12±1 mm while inhibition Gram-negative which is E. coli is 9.7±1.33 for raw extraction. Meanwhile, for curing extraction, only S.aureus shows a formation of zone of inhibition with 6.67±0.57 mm. For heated extraction, both bacteria strain show no zone of inhibition. This result will be very helpful as guidance for folks to choose the best preparation method for effective anti-bacteria effects.